Diversity, Frequency, and Persistence of Escherichia coli O157 Strains from Range Cattle Environments - Renter, David G.; Sargeant, Jan M.; Oberst, Richard D.; Samadpour, Mansour (My University, 2003)
Genetic diversity, isolation frequency, and persistence were determined for Escherichia coli O157 strains from range cattle production environments. Over the 11-month study, analysis of 9,122 cattle fecal samples, 4,083 water source samples, and 521 wildlife fecal samples resulted in 263 isolates from 107 samples presumptively considered E. coli O157 as determined by culture and latex agglutination. Most isolates (90.1%) were confirmed to be E. coli O157 by PCR detection of intimin and Shiga toxin genes. Pulsed-field gel electrophoresis (PFGE) of XbaI-digested preparations revealed 79 unique patterns (XbaI-PFGE subtypes) from 235 typeable isolates confirmed to be E. coli O157. By analyzing up to three isolates per positive sample, we detected an average of 1.80 XbaI-PFGE subtypes per sample. Most XbaI-PFGE subtypes (54 subtypes) were identified only once, yet the seven most frequently isolated subtypes represented over one-half of the E. coli O157 isolates (124 of 235 isolates). Recurring XbaI-PFGE subtypes were recovered from samples on up to 10 sampling occasions and up to 10 months apart. Seven XbaI-PFGE subtypes were isolated from both cattle feces and water sources, and one of these also was isolated from the feces of a wild opossum (Didelphis sp.). The number of XbaI-PFGE subtypes, the variable frequency and persistence of subtypes, and the presence of identical subtypes in cattle feces, free-flowing water sources, and wildlife feces indicate that the complex molecular epidemiology of E. coli O157 previously described for confined cattle operations is also evident in extensively managed range cattle environments.